2006
DOI: 10.1007/s00018-006-6240-2
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β transcriptionally activates the gene encoding the high-affinity adenosine transporter CNT2 in rat liver parenchymal cells

Abstract: The nucleoside transporter CNT2 is the highest-affinity adenosine transporter identified so far. Recent evidence suggests that CNT2 has functions other than salvage (i.e. modulation of purinergic responses). Here we identified TGF-beta1 as a potent inducer of CNT2 protein expression in liver parenchymal cells. By contrast, CNT1, which is a target of multifunctional cytokines involved in liver cell proliferation, does not respond to TGF-beta1 treatment. Cloning of a murine CNT2 gene sequence with promoter-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This observation does not prove by itself that CNT2 activation actually depletes the extracellular adenosine pool, but strongly supports the view that adenosine (and other purine nucleoside) pumping into liver parenchymal cells is activated by Ai receptors in an energy-dependent manner. CNT2 in this cell type is not a target of multifunciontal cytokines, such as TNF-u or IL-6, implicated in hepatocyte priming prior to cell cycle progression (18) but it is up-regulated, at the transcriptional level, by the proapoptotic agent TGF-~l (72). Overall, all these findings taken together strongly support a role for CNT2 far beyond salvage and nutrient absorption.…”
Section: Purinergic Regulationmentioning
confidence: 76%
“…This observation does not prove by itself that CNT2 activation actually depletes the extracellular adenosine pool, but strongly supports the view that adenosine (and other purine nucleoside) pumping into liver parenchymal cells is activated by Ai receptors in an energy-dependent manner. CNT2 in this cell type is not a target of multifunciontal cytokines, such as TNF-u or IL-6, implicated in hepatocyte priming prior to cell cycle progression (18) but it is up-regulated, at the transcriptional level, by the proapoptotic agent TGF-~l (72). Overall, all these findings taken together strongly support a role for CNT2 far beyond salvage and nutrient absorption.…”
Section: Purinergic Regulationmentioning
confidence: 76%
“…Information on the transcriptional regulation of CNT1 and CNT2 is still scarce. Hepatocyte nuclear factor 4␣ is known to modulate SLC28A1 gene expression in hepatocytes (Ferná ndez-Veledo et al, 2007;Klein et al, 2009), whereas the CNT2-encoding gene is transcriptionally activated by transforming growth factor-␤ (Valdés et al, 2006), CCAAT enhancer-binding protein ␣, hepatocyte nuclear factor 3␥ (Ferná ndez-Veledo et al, 2007), and hepatocyte nuclear factor 1␣ (Yee et al, 2009). Data from this study support a major role for RS1 in the trafficking of CNT proteins from the trans-Golgi network to the plasma membrane, without consistent proof of transcriptional modulation of the SLC28 genes.…”
Section: Discussionmentioning
confidence: 99%
“…A four-fold increase of adenosine transport activity and CNT2 molecular expression after treatment with dexamethasone was observed while no significant impact was noted from treatment with proliferative hormones [68] . However, a more recent paper by the same research group found that TGF-b can transcriptionally up-regulate CNT2 gene expression in rat hepatocytes [69] . Adenosine transpor t and CNT2 expression are altered during cell growth cycle and differentiation.…”
Section: Regulation Of Adenosine Transport and Cnt2 Expression In Genmentioning
confidence: 98%